الأمة المسلمة تكوين عقدي ومفهوم رسالي عالمي - Said, R. (Universiti Sains Islam Malaysia, 2024)
The paper defines, linguistically and technically, the concept of Muslim Ummah as human gathering with a common link, such as race, land, people , interest, goal and even religion. In Islam, this concept is very important and it is based on the idea of will and freedom of choice. However, without divine guidance, this concept could not be completely materialized. As a matter of fact, this divine guidance, in the form of true faith and religion structure, enable Muslims to congregate as brothers and interact effectively to form an ummah and rise to the apex of civilizations. This makes the Muslim Ummah the best and draws its human and universal functions to be good example amongst all nations. In this paper, this concept is studied analytically based on its use in the Arabic Language and Quran. Its principles and distinguishing features are also deducted from a number of related verses in the Quran, to highlight its relevance, validity and university in human life.